Residue-specific effects on slow inactivation at V787 in D2-S6 of Na(v)1.4 sodium channels. - O'Reilly, J P (2001)
Slow inactivation in voltage-gated sodium channels (NaChs) occurs in response to depolarizations of seconds to minutes and is thought to play an important role in regulating membrane excitability and action potential firing patterns. However, the molecular mechanisms of slow inactivation are not well understood. To test the hypothesis that transmembrane segment 6 of domain 2 (D2-S6) plays a role in NaCh slow inactivation, we substituted different amino acids at position V787 (valine) in D2-S6 of rat skeletal muscle NaCh mu(1) (Na(v)1.4). Whole-cell recordings from transiently expressed NaChs in HEK cells were used to study and compare slow inactivation phenotypes between mutants and wild type. V787K (lysine substitution) showed a marked enhancement of slow inactivation. V787K enters the slow-inactivated state approximately 100x faster than wild type (tau(1) approximately 30 ms vs. approximately 3 s), and occurs at much more hyperpolarized potentials than wild type (V(1/2) of s(infinity) curve approximately -130 mV vs. approximately -75 mV). V787C (cysteine substitution) showed a resistance to slow inactivation, i.e., opposite to that of V787K. Entry into the slow inactivation state in V787C was slower (tau(1) approximately 5 s), less complete, and less voltage-dependent (V(1/2) of s(infinity) curve approximately -50 mV) than in wild type. Application of the cysteine modification agent methanethiosulfonate ethylammonium (MTSEA) to V787C demonstrated that the 787 position undergoes a relative change in molecular conformation that is associated with the slow inactivation state. Our results suggest that the V787 position in Na(v)1.4 plays an important role in slow inactivation gating and that molecular rearrangement occurs at or near residue V787 in D2-S6 during NaCh slow inactivation.